Mid-term safe and effective profile of the Magmaris scaffold in percutaneous coronary intervention: a prospective, single-center study - Truong, Binh Quang; Tran, Hoa; Nguyen, Vinh Xuan; Nguyen, Chinh Duc; Nguyen, Khang Duong; Vu, Vu Hoang (Frontiers in Cardiovascular Medicine, 2023)
Significant advances have been made in the diagnosis and treatment of coronary artery disease over the years. New generations of scaffolds containing novel material and eluting drug have produced one of the most significant advancements in coronary intervention. The newest generation would be Magmaris with magnesium frame and sirolimus cover. From July 2018 to August 2020, 58 patients treated with Magmaris at University Medical Center Ho Chi Minh City were enrolled in this study. 60 lesions were stented, 60.3% of which were LAD lesions. There was no in-hospital event. Within 1 year after discharge, we noted 1 myocardial infarction event which required target-lesion revascularization; 1 stroke event, 1 non-target lesion revascularization patient, 1 target-vessel revascularization patient and 1 in-stent thrombosis. Among them, 1 myocardial infarction occurence, 1 non-target lesion revascularization and 1 in-stent thrombosis event were recorded within the first 30 days after discharge. In conclusion, the Magmaris scaffold is a safe and effective option for structural procedures performed with imaging device support, particularly intra-vascular ultrasound.